Development of STEAM-based Teaching Materials on Trigonometric Equations to Improve Students’ Mathematical Creative Thinking Ability - Rahardjoni, Amri Setiawan; Mashuri, Mashuri (Department of Mathematics, Universitas Negeri Semarang, 2022)
This research was a development research that aims to develop and to know the quality of Science, Technology, Engineering, Art, and Mathematics (STEAM)-based teaching materials viewed by the suitability of characteristics, validity, readability, and improvement of students’ mathematical creativity thinking ability. This research used the stages of Research and Development (R&D) those are: (1) potential and problems; (2) data collection; (3) product design; (4) product test (readability test); (5) trial test; (6) final product. The result showed that the teaching material met the suitability of the characteristic. The result of the validity test showed a percentage of 89.3%. The readability test result showed a percentage of 74.8%. The analysis of the pretest and posttest showed that teaching materials could improve students’ mathematical creativity thinking ability with the N-Gain score of 0.34 in the medium category. Therefore, the Science, Technology, Engineering, Art, and Mathematics (STEAM)-based teaching materials is qualified.